IZAK CORNELIUS, The Many Faces of the Goddess. The Iconography of the SyroPalestinian Goddess Anat, Astarte, Qedeshet, and Asherah c. 1500-1000 BCE. Orbis Biblicus et Orientalis 204. Fribourg: Academic Press Fribourg/Vandenhoeck & Ruprecht Göttingen, 2008, 207 pp. ISBN 3-7278-1485-3. Second, enlarged edition. € 59.00 - Bornapé Muñoz, Allan Rodrigo (2010)
Fil: Bornapé Muñoz, Allan Rodrigo. Universidad Adventista de Chile; Chile